MULTITUDE EFFECT OF ALUMINIUM SULFATE-DOPED TIO2 PASSIVATION PHOTOELECTRODE FOR PERFORMANCE ENHANCEMENT OF DYE-SENSITIZED SOLAR CELLS, DSSCS - A.M. SHAHRUL, M.H. ABDULLAH, M.H. MAMAT, N.D. MD SIN, E. NOORSAL, AGUS SUPRIYANTO (TPM – Testing, Psychometrics, Methodology in Applied Psychology, 2025)
In this study, aluminum sulphate hydrate, Al2(SO4)3-doped TiO2 based passivation photoelectrode (ADTP) was successfully proved to be a promising method of improving DSSCs. Here, ADTP based photoelectrodes were obtained by varying the percentages of Al2(SO4)3 added to the nanoparticles of Titanium dioxide (TiO2). The morphological images of the ADTPs obtained using field emission scanning electron micrograph (FESEM) indicate their compositional behavior, which include two different sizes (different atomic radii) of titanium and aluminium nanoparticles. Furthermore, the occurrence of the Ti4+/Al3+ ions substitution in the ADTP film was then supported by UV-Vis spectroscopy analysis. Meanwhile, the fourier transform infrared (FTIR) spectroscopy analysis revealed that the ADTP samples have higher OH- functional group which is attributed to the formation of the Al(OH)3 mediators. These mediators enhance the binding of dye molecules to the TiO2 nanoparticles, thereby improving the adsorption of the dye molecules onto the ADTP surfaces. The subsequent electrochemical impedance spectroscopy (EIS) analysis revealed that all ADTP photoelectrodes exhibited higher conductivity TiO2 film and trap states, which serves for lower interfacial resistance, inhibiting back recombination and promoting more carriers for electron conduction (photocurrent density, JSC). The integrated properties of the ADTP photoelectrode that improve interfacial resistance, induce higher dye adsorption and reduce back electron recombination resulted in a 0.47 % increase in power conversion efficiency (PCE) of the 3-ADTP-based DSSC.